Integrating realistic mathematics education and deep-learning approaches into an e-comic - Putri, Febby Ayuni Esya; Febriani, Ditia Erika; Parandrengi, Resyarusyda (Primatika : Jurnal Pendidikan Matematika, 2025)
At the upper primary level, mathematics becomes more abstract and can be particularly difficult for students, especially when learning integers. Teachers, therefore, need effective media to support students’ conceptual understanding. One such medium is the use of e-comics that integrate real-life contexts through the Realistic Mathematics Education (RME) approach and are supported by deep-learning principles to promote deeper understanding. This study explores teachers’ and students’ responses to the use of RME- and deep-learning-based e-comics in classroom learning and examines their effectiveness in improving students’ understanding of integer concepts, in SDN 188/IV Jambi. Data were collected using practical questionnaires, pre- and post-tests, and interviews. Quantitative data were analyzed descriptively and using N-gain analysis, while qualitative data were analyzed through data reduction and interpretation. The results indicate that the e-comic is practical for classroom use and effective in enhancing students’ conceptual understanding.